Elective freezing of embryos versus fresh embryo transfer in IVF: a multicentre randomized controlled trial in the UK (E-Freeze). Issue 3 (6th January 2022) - Maheshwari, Abha; Bell, Jennifer L; Bhide, Priya; Brison, Daniel; Child, Tim; Chong, Huey Yi; Cheong, Ying; Cole, Christina; Coomarasamy, Arri; Cutting, Rachel; Hardy, Pollyanna; Hamoda, Haitham; et al.
Abstract: STUDY QUESTION: Does a policy of elective freezing of embryos, followed by frozen embryo transfer result in a higher healthy baby rate, after first embryo transfer, when compared with the current policy of transferring fresh embryos? SUMMARY ANSWER: This study, although limited by sample size, provides no evidence to support the adoption of a routine policy of elective freeze in preference to fresh embryo transfer in order to improve IVF effectiveness in obtaining a healthy baby. WHAT IS KNOWN ALREADY: The policy of freezing all embryos followed by frozen embryo transfer is associated with a higher live birth rate for high responders but a similar/lower live birth after first embryo transfer and cumulative live birth rate for normal responders. Frozen embryo transfer is associated with a lower risk of ovarian hyperstimulation syndrome (OHSS), preterm delivery and low birthweight babies but a higher risk of large babies and pre-eclampsia. There is also uncertainty about long-term outcomes, hence shifting to a policy of elective freezing for all remains controversial given the delay in treatment and extra costs involved in freezing all embryos. STUDY DESIGN, SIZE, DURATION: A pragmatic two-arm parallel randomized controlled trial (E-Freeze) was conducted across 18 clinics in the UK from 2016 to 2019. A total of 619 couples were randomized (309 to elective freeze/310 to fresh). The primary outcome was a healthy baby after first embryo transfer (term, singleton live birth with appropriate weight for gestation); secondary outcomes included OHSS, live birth, clinical pregnancy, pregnancy complications and cost-effectiveness. PARTICIPANTS/MATERIALS, SETTING, METHODS: Couples undergoing their first, second or third cycle of IVF/ICSI treatment, with at least three good quality embryos on Day 3 where the female partner was ≥18 and <42 years of age were eligible. Those using donor gametes, undergoing preimplantation genetic testing or planning to freeze all their embryos were excluded. IVF/ICSI treatment was carried out according to local protocols. Women were followed up for pregnancy outcome after first embryo transfer following randomization. MAIN RESULTS AND THE ROLE OF CHANCE: Of the 619 couples randomized, 307 and 309 couples in the elective freeze and fresh transfer arms, respectively, were included in the primary analysis. There was no evidence of a statistically significant difference in outcomes in the elective freeze group compared to the fresh embryo transfer group: healthy baby rate {20.3% (62/307) versus 24.4% (75/309); risk ratio (RR), 95% CI: 0.84, 0.62 to 1.15}; OHSS (3.6% versus 8.1%; RR, 99% CI: 0.44, 0.15 to 1.30); live birth rate (28.3% versus 34.3%; RR, 99% CI 0.83, 0.65 to 1.06); and miscarriage (14.3% versus 12.9%; RR, 99% CI: 1.09, 0.72 to 1.66). Adherence to allocation was poor in the elective freeze group. The elective freeze approach was more costly and was unlikely to be cost-effective in a UK National Health Service context. LIMITATIONS, REASONS FOR CAUTION: We have only reported on first embryo transfer after randomization; data on the cumulative live birth rate requires further follow-up. Planned target sample size was not obtained and the non-adherence to allocation rate was high among couples in the elective freeze arm owing to patient preference for fresh embryo transfer, but an analysis which took non-adherence into account showed similar results. WIDER IMPLICATIONS OF THE FINDINGS: Results from the E-Freeze trial do not lend support to the policy of electively freezing all for everyone, taking both efficacy, safety and costs considerations into account. This method should only be adopted if there is a definite clinical indication. STUDY FUNDING/COMPETING INTEREST(S): NIHR Health Technology Assessment programme (13/115/82). This research was funded by the National Institute for Health Research (NIHR) (NIHR unique award identifier) using UK aid from the UK Government to support global health research. The views expressed in this publication are those of the author(s) and not necessarily those of the NIHR or the UK Department of Health and Social Care. J.L.B., C.C., E.J., P.H., J.J.K., L.L. and G.S. report receipt of funding from NIHR, during the conduct of the study. J.L.B., E.J., P.H., K.S. and L.L. report receipt of funding from NIHR, during the conduct of the study and outside the submitted work. A.M. reports grants from NIHR personal fees from Merck Serono, personal fees for lectures from Merck Serono, Ferring and Cooks outside the submitted work; travel/meeting support from Ferring and Pharmasure and participation in a Ferring advisory board. S.B. reports receipt of royalties and licenses from Cambridge University Press, a board membership role for NHS Grampian and other financial or non-financial interests related to his roles as Editor-in-Chief of Human Reproduction Open and Editor and Contributing Author of Reproductive Medicine for the MRCOG, Cambridge University Press. D.B. reports grants from NIHR, during the conduct of the study; grants from European Commission, grants from Diabetes UK, grants from NIHR, grants from ESHRE, grants from MRC, outside the submitted work. Y.C. reports speaker fees from Merck Serono, and advisory board role for Merck Serono and shares in Complete Fertility. P.H. reports membership of the HTA Commissioning Committee. E.J. reports membership of the NHS England and NIHR Partnership Programme, membership of five Data Monitoring Committees (Chair of two), membership of six Trial Steering Committees (Chair of four), membership of the Northern Ireland Clinical Trials Unit Advisory Group and Chair of the board of Oxford Brain Health Clinical Trials Unit. R.M. reports consulting fees from Gedeon Richter, honorarium from Merck, support fees for attendance at educational events and conferences for Merck, Ferring, Bessins and Gedeon Richter, payments for participation on a Merck Safety or Advisory Board, Chair of the British Fertility Society and payments for an advisory role to the Human Fertilisation and Embryology Authority. G.S. reports travel and accommodation fees for attendance at a health economic advisory board from Merck KGaA, Darmstadt, Germany. N.R.-F. reports shares in Nurture Fertility. Other authors' competing interests: none declared. TRIAL REGISTRATION NUMBER: ISRCTN: 61225414. TRIAL REGISTRATION DATE: 29 December 2015. DATE OF FIRST PATIENT'S ENROLMENT: 16 February 2016.